2022
DOI: 10.17678/beuscitech.1203542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of architectural heritage characteristics and seismic behavior of Ziyaeddin Han Tomb

Abstract: Historical buildings built by different civilizations that have survived to the present day have an important place within the scope of the protection of cultural heritage. Bitlis province, where many different civilizations lived and located in a strategic position on the Silk Road, contains many different types of historical structures. Within the scope of this study, the Ziyaeddin Han Tomb, which was built in masonry during the Ottoman period, has been taken into account. Besides the architectural features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…After analyzing 3 historical palaces with the finite element models, Valente ve Milani [18] studied the crack development, earthquake behavior with nonlinear dynamic analysis, and made a general assessment of damage and collapse. Karaton et al examined the earthquake behavior of historical Malabadi bridge, which was built in the 12th century and located in the east of Turkey, for different earthquake levels [25]. As a result of the study, D1, D2 and D3 are from the lowest to the highest ground motion level, no significant damage occurred at the ground motion levels D1 and D2; it was observed that the historic bridge suffered substantial damage at the D3 ground motion level.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing 3 historical palaces with the finite element models, Valente ve Milani [18] studied the crack development, earthquake behavior with nonlinear dynamic analysis, and made a general assessment of damage and collapse. Karaton et al examined the earthquake behavior of historical Malabadi bridge, which was built in the 12th century and located in the east of Turkey, for different earthquake levels [25]. As a result of the study, D1, D2 and D3 are from the lowest to the highest ground motion level, no significant damage occurred at the ground motion levels D1 and D2; it was observed that the historic bridge suffered substantial damage at the D3 ground motion level.…”
Section: Introductionmentioning
confidence: 99%